2008
DOI: 10.2310/jim.0b013e3181891512
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic Polymorphisms (TGF-β, PAI-1, AT) in Mexican Patients with Established Liver Fibrosis. Potential Correlation with Pirfenidone Treatment

Abstract: Our data suggested that a combination of inherited polymorphisms increased the risk of advanced fibrosis in ELF patients. Pure HCV and pure alcohol consumption patients which were homozygous G/G carriers had 19.5- and 10.8-fold higher risk to develop advanced fibrosis respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…The G→C transition at position 915 of the TGF-β1 signal sequence causes the amino acid sequence to change from arginine to proline in codon 25. A number of previous studies reported the association between this SNP and susceptibility to chronic HCV infection (14)(15)(16)(17)(18)(19)(20)(21). However, the currently available results are controversial.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…The G→C transition at position 915 of the TGF-β1 signal sequence causes the amino acid sequence to change from arginine to proline in codon 25. A number of previous studies reported the association between this SNP and susceptibility to chronic HCV infection (14)(15)(16)(17)(18)(19)(20)(21). However, the currently available results are controversial.…”
Section: Introductionmentioning
confidence: 78%
“…Stimulating the leucocytes of patients with the GG genotype in vitro was shown to produce significantly more TGF-β1 compared to individuals with the GC genotype (39). Therefore, the association between the SNP in TGFB1 and susceptibility to chronic HCV infection was investigated by several researchers, yielding, however, inconsistent conclusions (14)(15)(16)(17)(18)(19)(20)(21). To the best of our knowledge, this is the first meta-analysis performed to assess the association between TGFB1 915G/C polymorphism and susceptibility to chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations